Blunt Cerebrovascular Injuries: A review of the literature - Al-Harthy, Abdullah (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2011)
Blunt cerebrovascular injuries (BCVI) have been a topic of interest to many researchers worldwide as evidenced by the vast amount of available literature. The interest in these rare injuries is probably due to the significant possibility of mortality and morbidity amongst patients who sustain them, when the employment of radiological screening methods could prevent such an outcome. Recognition of these injuries is the most important step towards prevention of adverse outcomes. We present a comprehensive review of the literature regarding the mechanism of injury, imaging, management, and complications of BCVI. Articles were identified through a search of MEDLINE and the Cochrane Central Register of Controlled Trials using the keywords Blunt; Vascular; Carotid; Vertebral; Trauma; Stroke; Management, and Endovascular. The search was limited to humans and articles in English.